2020
DOI: 10.3390/agronomy10010064
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of 10 Spring Camelina Genotypes Grown in Environmental Conditions in North-Eastern Poland

Abstract: Camelina (Camelina sativa (L.) Crantz) is an alternative oilseed crop that is garnering increasing popularity due to its multiple applications and greater tolerance to adverse environmental conditions than oilseed rape. The study analyzed selected traits of 10 Canadian and Polish spring camelina genotypes grown in a field experiment in north-eastern Poland in 2015–2018. The greatest differences were observed in seed yield where the effect of weather and environmental conditions explained 72.7% of variance, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…Currently, interest in the study and cultivation of camelina is shown in Europe, Canada, the United States and other countries of the world [4][5][6][7][8][9][10]. In European countries, the yield of camelina amounts to: 1.9 t/ha in Germany, 2.8 t/ha in France [7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, interest in the study and cultivation of camelina is shown in Europe, Canada, the United States and other countries of the world [4][5][6][7][8][9][10]. In European countries, the yield of camelina amounts to: 1.9 t/ha in Germany, 2.8 t/ha in France [7].…”
Section: Introductionmentioning
confidence: 99%
“…1b) until the formation of a rosette (Martinelli and Galasso 2011). Camelina can reach a final height ranging from 0.65 to 1.05 m (Czarnik et al 2018;Jankowski et al 2019;Masella et al 2014;Vollmann et al 2007;Załuski et al 2020) and form up to 30 lateral branches ( Fig. 1c) (Martinelli and Galasso 2011).…”
Section: Morphological Description and Main Agronomic Traitsmentioning
confidence: 99%
“…Each silique can contain 10-20 small seeds (Czarnik et al 2017;Jankowski et al 2019;Martinelli and Galasso 2011). In fact, 1000-seed weight varies from 0.7 to 1.8 g (Angelini et al 1997;Czarnik et al 2017Czarnik et al , 2018Jankowski et al 2019;Righini et al 2019;Vollmann et al 2007;Załuski et al 2020;Zanetti et al 2017;Zubr 1997). Older studies report a negative correlation between seed weight and both seed and oil yield.…”
Section: Morphological Description and Main Agronomic Traitsmentioning
confidence: 99%
See 2 more Smart Citations